Dental Discomfort Questionnaire: assessment of dental discomfort and/or pain in very young children - Versloot J, Veerkamp JSJ, Hoogstraten J. (Blackwell Synergy, 2006)
To present and analyse the Dental Discomfort Questionnaire (DDQ) for very young children and to assess the possible differences in pain-related behaviours displayed by children with or without reported toothache, and by children with or without decayed teeth.